Transit border lives and blurring solidarities - Ribas-Mateos, Natalia (Frontiers in Human Dynamics, 2025)
This article discusses Transit Border Lives and Blurring Solidarities in relation to the main findings presented in the book “A Message to You. A Cartography of Mobilities. Sexual Border Violence, Solidarities, and Global Cities”. The methodology is based on various video debates (videos filmed in the Mediterranean and shown in London and Paris), which reveal the complexities of sexual border violence and contemporary solidarities. The majority of the participants in the debates deflect criticism from themselves by blaming the law, international bodies, and EU migration policies—never themselves—highlighting the need for greater reflexivity. Diversity and diaspora are examined in the context of global cities. The multi-situated, participatory study, which employs a visual anthropology approach and a “grounded research” methodology, raises numerous questions that are also explored in the debates. Topics covered include the selection of fieldwork, with references to other movements such as Black Lives Matter (BLM), Me Too, and cancel culture. The main question of the article involves a recalibration of the meaning of sexual violence in transit within the construction of modernity. It invites us to explore forms of domination—or total domination—in how we conceive extreme violence in places such as borders. Second, it calls into question feminist and diaspora movements in their positioning of women’s stories, examining how politics, sexual violence, and mobilities intersect in the Mediterranean context. The responses are characterized as “blurring solidarities,” a concept that seeks to capture the mixture of actions organized under the umbrella of solidarity while highlighting the tensions between solidarity and neoliberalism. This theme is central in these neoliberal times, driven by the question of whom to identify with (e.g., women, diaspora, Afro-diasporic thought, migrants, and activists) and where the challenge is placed within feminism. How can new research contribute to a renewal of feminist thinking? Briefly, this form of “total domination” in discussions of sexual border violence and feminist responses underscores significant differences and fragmentations within solidarity. Under “transit conditions,” we present “border sexual violence” as intertwined with an understanding of extreme violence, suffering, and solidarity. This cartography of mobilities is also affected by major shifts, such as the sociology of globalization (scales—global cities and border cities, transnational activism, and feminist activism), the mobility turns (social sciences and especially the sociology of mobilities and its connection with global migration), and the nuances of the Afro-topic conception (regarding the multiple forms of integrating African knowledge into mainstream research).